The headscarf and the veil in English courts of law: issues of free expression and proportionality - Candlish, John (IIUM Press, 2009)
Introduction: This chapter confines itself to strictly legal issues arising form the cases of Aishah Azmi and Shahina Begum, with some comments on the recent use of 'X' as well as, peripherally, some related aspects......